MENGUNTUNGKANKAH BERBISNIS INDUSTRI PANGAN LOKAL? STUDI KASUS UMKM YULIWARDI KOTO TUO PADANG - Dian Hafizah; Rini Hakimi; Elpakhri Penawan; Azmi Boy (Jurusan Agribisnis, Fakultas Pertanian, Perikanan dan Biologi Universitas Bangka Belitung, 2023)
Local Food Commodities are still underutilized as raw materials for industry and other business activities. One of the entrepreneurs who uses local food commodities as raw materials for their business is MSME Yuliwardi which is engaged in providing snack boxes. The local foodstuffs it uses are purple sweet potatoes, cassava and others. With various creations and innovations, it has removed the stigma that doing business in the local food-based food sector is not profitable. For this reason, the purpose of this study is to analyze Yuliawardi's MSME business whether it is profitable or not. The method used is variable costing. From the research that has been carried out, it is found that Yuliwardi MSMEs have been running for 7 years starting from 2015. The initial capital was obtained through a loan to Nagari Bank. Raw Material Suppliers are obtained from farmers around the place of business and limes of Manis and its surroundings. Payment is made in cash directly upon pick-up of the goods. The total operating profit per month from the sale of boss products and snacks is IDR 26,203,300 with details of total receipts of IDR 79,065,000 and Fixed Costs of IDR 229,200 and Variable Costs of IDR 39,532,500. Conclusion Local food-based industries are very profitable to strive for and provide great profits.